Analyzing The Effect Of Bank Characteristic On Profitability In Banking Companies Listed In Indonesia Stock Exchange - Serly Serly (Fakultas Ekonomi Universitas Kadiri, 2021)
This research is conducted to analyze the effect of bank characteristics on go public banks’ profitability in Indonesia. Return on asset, return on equity, and net interest margin are dependent variables in this research and involves five types of banking risks (credit, liquidity, security, capital, and insolvency), bank size and diversification, and cost efficiency. Research objects of this research are banking companies listed on Indonesian Stock Exchange (IDX). The research data is financial data issued by IDX from 2014 to 2018. Observation data collected in this research is processed using the regression panel method. The result from this research is that credit risk and insolvency risk has effect on return on asset and return on equity significantly. Liquidity risk, capital risk and bank size don’t have significant effect. Security risk and bank diversification effecting net interst margin significantly. Cost efficiency has effect on profitability significantly.